Genel İşlem Koşullarında Saydamlık Kuralının, Bunun TBK m. 20 vd.’daki Görünümlerinin ve TTK m. 55 f. 1 f ile TBK m. 20 vd.’nın Birlikte Uygulanabilirliğinin Değerlendirilmesi - (:unkn) unknown (My University, 2018)
Genel işlem koşulları birçok yararlı fonksiyonlar içermesi yanında kötüye kullanılma riski de taşır.Dürüstlük kuralına aykırı genel işlem koşulu kullanımının sözleşmeler hukuku yanında rekabet hukukunailişkin bir yönü bulunmaktadır. Bu bağlamda saydamlık kuralı da genel işlem koşulu hukukunun gelişimisırasında yaşanan en önemli yenilik ve prensiplerinden biri olarak kabul edilmektedir. Bu makalede ilkolarak saydamlık kuralının tanımı, fonksiyonları aktarılacak. Daha sonra saydamlık kuralının TBK m. 20vd.’daki anlamı değerlendirilecektir. Makalemizin son bölümünde ise ticari standart sözleşmelerde TTKm. 55 f. 1 f ile TBK m. 20 vd.’nın birlikte uygulanabilirliği değerlendirilecektir.

General terms and conditions include the risk of being abused in addition beneficial functions. Application of general terms against the principle of honesty has different perspectives regarding contract law and competition law. In this context the principle of transparency as generally accepted ist the most important novelty and principle in the development of the law of general term. In this article first of all the definition, functions of the principle of transparency will be explained. Afterwards the meaning of the principle of transparency in TOC Article 20 ff. will be examined. In the last section of our articles combined applicability of TCC Article 55/1-f with TOC article 20 ff. in commercial standard contracts will be analyzed.
(Evaluation of the Principle of Transparency in General Terms and Conditions, its Appearance in TOC Article 20 ff. and Combined Applicability of TCC Article 55/1-f With TOC Article 20 ff. in Commercial Standart Contracts)
Keywords: Hukuk